Trajectory of Systemic Blood Pressure in Early Life: A Cohort Study - Norrara Scarlytt de Oliveira Holanda BA; Maria Clara Lima da Cruz BA; Cynthia Cibelle dos Santos Xavier BA; Valeria Azevedo de Almeida MS; Cristiane Aparecida Moran PhD; Ingrid Guerra Azevedo PhD; Adriele de Morais Nunes MS; Silvana Alves Pereira PhD (SAGE Publishing, 2023)
Objective . To track the BP (blood pressure) trajectory of healthy infants during the first year of life of healthy infants born in Northeast Brazil. Methods . In this cohort study, BP was assessed by oscillometry at the first 24 hours of life and 12 months of age. Results . Systolic blood pressure (SBP) and diastolic blood pressure (DBP) increased with age ( P  < .001) and were not influenced by gender (SBP: P  = .178 and DBP: P  = .623) or type of delivery (SBP: P  = .827 and DBP: P  = .106), when compared between the first 24 hours of life and 12 months of age. Conclusion . The data from the present study increased knowledge about the trajectory of BP during the first year of life. The increase in BP between the first month and the first year of life was not influenced by gender or type of delivery.